A Reconfigurable Power-Efficient Quantized Analog RF Front-End With Smart Calibration - Justin Yonghui Kim; Antonio Liscidini (IEEE Open Journal of the Solid-State Circuits Society, 2022)
A power-scalable RF front-end using quantized analog signal processing is presented. The front-end is based on a voltage-mode power-scalable approach which allows the power dissipation to be scaled upon the operative scenario and to perform an agile calibration for mismatch impairments. Power and input dynamic range can be scaled upon the desired 1-dB compression point (1dBCP) (from −15.3 to 0.5 dBm) while keeping the same sensitivity with 2.5-dB NF. Signal path power can vary between 3.3 and 6.4 mW while clock generation and distribution power can vary between 1.6 and 18.5 mW/GHz, with a phase noise as low as −171.2 dBc/Hz. After calibration, IM2 and IM3 improved up to 33 dB while 1dBCP improved by 1 dB, which resulted in achieving an IIP3 of 26.1 dBm and IIP2 of 71 dBm at 0-dBm 1dBCP.